Sodium nitroprusside an ethylene reduction inducer. An alternative that prolongs the shelf life of cut inflorescences of Dendrobium orchids - Ramin Mohammadpour; Mantana Buanong; Pongphen Jitareerat; Chalermchai Wongs-Aree; Apiradee Uthairatanakij (Journal of the Selva Andina Research Society)
Nitric oxide has been identified as a chemical compound that can prolong the vase life of various cut flowers. The effects of sodium nitroprusside, a nitric oxide donor, on 1-aminocyclopropane-1-carboxylate synthase and 1-aminocyclopropane-1-carboxylic Acid oxidase activities, ethylene production, respiration, bud opening, and electrolyte leakage and lipid peroxidation during post-harvest storage of cut inflorescences of Dendrobium cv. “Planty Fushia” orchid were evaluated. Inflorescences kept in 10 µmol L-1 sodium nitroprusside solution at room temperature (23±2°C) had longer vase life compared to controls in distilled water. Sodium nitroprusside increased vase life due to 1-aminocyclopropane-1-carboxylate synthase and 1-aminocyclopropane-1-carboxylic acid oxidase a activities in buds and open flowers, thereby reducing ethylene production. Electrolyte leakage, malondialdehyde and respiration were also lower in plants treated with sodium nitroprusside compared to controls. In addition, sodium nitroprusside treatment increased the percentage of buds that opened. Therefore, sodium nitroprusside can be used to prolong the vase life of cut inflorescences of Dendrobium for 4 days at room temperature. The results indicate that sodium nitroprusside solution significantly affected the vase life of cut inflorescences of Dendrobium, 10 µmol L-1 sodium nitroprusside could significantly increase bud opening and prolong vase life compared to the control.